Legal Reform of Copyright in the Digital Economy Era within the Paradigm of Pancasila Justice - Eddie Bachtiar Siagian; Mulyono; Hulman Panjaitan (MSJ : Majority Science Journal, 2025)
Copyright law reform in the digital economy era is an urgent need to maintain the consistency of Indonesia's state ideology, particularly in the face of globalization and the dominance of purely economic interests. The main problem in this study is the lack of alignment between business actors and government institutions regarding copyright, as well as the weak implementation of Pancasila values in copyright regulations. This study aims to analyze how the principles of social justice of Pancasila can be applied in copyright law reform amidst the development of the digital economy. The method used is a juridical-normative approach with a qualitative analysis of laws and regulations, related policies, and expert views through literature studies. The results of the study indicate that the dominant economic orientation in copyright regulation tends to ignore the values of humanity and social justice. Furthermore, the lack of synergy between the government and business actors leads to weak legal effectiveness. Therefore, it is necessary to reformulate policies that support Pancasila values, as well as strengthen human resource capacity so that copyright law can become a fair and ethical instrument in the digital era.